Cyclin A activates the DNA polymerase δ-dependent elongation machinery in vitro: a parvovirus DNA replication model - Bashir, Tarig; Rommelaere, Jean (Proceedings of the National Academy of Sciences of the United States of America, 2000)
Replication of the single-stranded linear DNA genome of parvovirus minute virus of mice (MVM) starts with complementary strand synthesis from the 3′-terminal snap-back telomere, which serves as a primer for the formation of double-stranded replicative form (RF) DNA. This DNA elongation reaction, designated conversion, is exclusively dependent on cellular factors. In cell extracts, we found that complementary strand synthesis was inhibited by the cyclin-dependent kinase inhibitor p21WAF1/CIP1 and rescued by the addition of proliferating cell nuclear antigen, arguing for the involvement of DNA polymerase (Pol) δ in the conversion reaction. In vivo time course analyses using synchronized MVM-infected A9 cells allowed initial detection of MVM RF DNA at the G1/S phase transition, coinciding with the onset of cyclin A expression and cyclin A-associated kinase activity. Under in vitro conditions, formation of RF DNA was efficiently supported by A9 S cell extracts, but only marginally by G1 cell extracts. Addition of recombinant cyclin A stimulated DNA conversion in G1 cell extracts, and correlated with a concomitant increase in cyclin A-associated kinase activity. Conversely, a specific antibody neutralizing cyclin A-dependent kinase activity, abolished the capacity of S cell extracts for DNA conversion. We found no evidence for the involvement of cyclin E in the regulation of the conversion reaction. We conclude that cyclin A is necessary for activation of complementary strand synthesis, which we propose as a model reaction to study the cell cycle regulation of the Pol δ-dependent elongation machinery.
Gesehen am 15.02.2021